Building A Moderate Muslim Generation: Strategic Analysis Of KMA 450/2024 In Preventing Radicalism In Madrasah Ibtidaiyah - Dedy Irawan; Khairil Anwar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Background: This research examines the strategic role of KMA 450/2024 (Decree of the Minister of Religious Affairs Number 450 of 2024) in building a moderate Muslim generation and preventing radicalism through madrasah ibtidaiyah education in Indonesia. With the largest Muslim population globally, Indonesia faces challenges from religious radicalism, particularly among youth aged 15-30 years who are vulnerable to radical ideologies spreading through digital platforms. Method: Using a qualitative descriptive approach based on document analysis, this research examines how radicalism prevention strategies are integrated into KMA 450/2024, what strategies are developed to build a moderate Muslim generation, and the implications for madrasah ibtidaiyah education. The findings reveal that KMA 450/2024 integrates radicalism prevention and religious moderation through three main dimensions: the integration of P5RA (Profile of Pancasila Students and Rahmatan lil Alamin) that develops wasathiyyah values, a flexible and contextual curriculum structure, and a focus on developing moderate Islamic character. In building a generation of moderate Muslims, the policy develops three key strategies: implementation of P5RA Projects based on Islam Rahmatan lil Alamin values, development of integrated thematic learning incorporating religious moderation values, and building a balance between religious and citizenship values to foster mutual respect in diversity. The implementation of KMA 450/2024 has significant implications: strengthening a systemic approach to address exclusivism at the root of radicalism, increasing the need for educator capacity in teaching religious moderation values, and reinforcing an educational ecosystem that supports inclusive character formation. Conclusion: The research concludes that KMA 450/2024 represents a strategic step in preventing radicalism through the internalization of religious moderation in madrasah ibtidaiyah education. Optimizing implementation requires developing contextual P5RA operational guidelines, enhancing educator capacity, and conducting evaluative research to continuously improve radicalism prevention efforts in Indonesia's madrasah ibtidaiyah education environment.